Disseminated Mycobacterium tuberculosis: An Unusual Presentation with Associated Hemophagocytic Lymphohistiocytosis. (27th January 2022) - Arfa, Ahmed; Omar, Nivin; Bano, Kulsum; Savage, Natasha M.
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially fatal, and systemic hyperinflammatory syndrome with exacerbated and uncontrolled activation of histiocytes and lymphocytes against mature cells. Secondary HLH can occur in association with a myriad of underlying infections or malignancies. Our patient is a 38-year-old male prisoner with poorly controlled diabetes and no known other medical conditions. He was referred to our emergency department with three-week history of worsening malaise, weight loss, fever, bruising, and shortness of breath; imaging showed pneumomediastinum, lung nodule, and adrenal mass. Biopsy of the lung nodule revealed acid-fast bacilli. Furthermore, bone marrow biopsy showed foci of necrosis with associated acid-fast bacilli and hemophagocytosis highlighted by CD163 stain; consequently, secondary HLH was suggested. Hence, lab results were reviewed and found to satisfy five of the eight secondary HLH criteria. Moreover, ferritin was >10, 000 ng/ml, which has been suggested to be highly suspicious for HLH. The patient was started on anti-MAC therapy. Unfortunately, the patient's status declined rapidly; he developed multi-organ failure and succumbed to disease. Later, his culture confirmed Mycobacterium tuberculosis . In conclusion, we presented a rare and challenging case of secondary HLH associated with disseminated Mycobacterium tuberculosis . A high index of suspicion is required for early diagnosis and treatment, and pathologists should be aware of Mycobacterium tuberculosis ' association with secondary HLH.